PARTISIPASI MASYARAKAT TERHADAP PELAKSANAAN PROGRAM KAMPUNG IKLIM (PROKLIM) - Nur Kholipah, Siti; Liviyani, Leni; Maulana NH, Rizki; Karwati, Lilis (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Climate change is one of the global problems currently being faced by the world. Indonesia is one of the countries that is vulnerable to the impacts of climate change. The Climate Village Program (Proklim) is one of the efforts made by the government to reduce the impact of climate change. Community participation is an important factor in the successful implementation of Proklim. Community participation can be interpreted as community involvement in all stages of program implementation, starting from planning, implementation, evaluation and utilization of results. This research aims to analyze community participation in the implementation of Proklim in Palasari Hamlet, Sukahurip Village, Cihaurbeuti District, Ciamis Regency, West Java. This research uses qualitative research methods. Research data was obtained through in-depth interviews with sources, observation and documentation. The research results show that community participation in implementing Proklim in Palasari Hamlet has gone well. Community participation has been visible since the planning, implementation and utilization stages. At the planning stage, the community is involved in providing ideas and thoughts about the activities that will be carried out in Proklim. At the implementation stage, the community is involved in implementing Proklim activities, such as planting trees, building infiltration wells, and composting. At the harvest utilization stage, the community feels the benefits of Proklim activities, such as the availability of clean water, cleaner air, and increased agricultural productivity. However, there are still several things that need to be improved in the implementation of Proklim in Palasari Hamlet, namely the need to increase community capacity in implementing Proklim activities and the need for support from the regional government and central government.